Lärmwirkungen von Infraschallimmissionen. Abschlussbericht - Krahé, Detlef; Di Loro, Alexander Alaimo; Müller, Uwe; Elmenhorst, Eva-Maria; De Gioannis, Riccardo; Schmitt, Stefan; Belke, Christin; Benz, Sarah; Großarth, Stephan; Schreckenberg, Dirk; Eulitz, Christian; Wiercinski, Bianca; et al. (My University, 2020)
Die akustische Belastung der Menschen verändert sich. Wachsende Mobilität, steigender Siedlungsdruck und die Energiewende tragen zu neuen Umweltbedingungen bei. Hierzu zählen auch Geräusche von technischen Anlagen, die tieffrequenten Schall einschließlich Infraschall emittieren. Infraschall kennzeichnet auf Grund seiner Schallwellen im Frequenzbereich unter 20 Hertz die Eigenschaft, dass er definitionsgemäß außerhalb des für den Menschen mit dem Gehör wahrnehmbaren Bereichs liegt. Das Forschungsvorhaben untersucht mit Hilfe einer Laborstudie den Zusammenhang zwischen der kurzzeitigen Exposition durch verschiedene Infraschallgeräusche und akuten körperlichen Reaktionen sowie dem Lästigkeitsempfinden.

Over the last few years, increasing development pressure has had a profound influence on the acoustics of the environment. This may also affect the way we perceive annoyance. Ongoing technical noise from stationary equipment and installations has caused new environmental conditions. Public debate is focusing increasingly on the negative impact on residents, caused by equipment and installations emitting infrasound. In many cases reference is made to what is deemed an inadequate level of protection, and affected persons are demanding more stringent noise abatement measures. The present publication investigates the following issue: What kind of physiological or psychological effects does infrasound cause in the test subjects? The subject of this survey was whether infrasound immissions will be judged as annoying or uncomfortable, on the one hand. On the other hand, measurable and acute reactions on the bodies of the test subjects were also investigated.
Noise effect of infrasound immissions.
Keywords: Infraschall; Immission; Gesundheitsgefährdung; Gefährdungsanalyse; Empirische Untersuchung